Clinical Application of Mesenchymal Stem Cells in the Treatment and Prevention of Graft-versus-Host Disease - Yi Lin; William J. Hogan (Advances in Hematology)
Mesenchymal stem cells (MSCs) represent a heterogeneous population of stromal cells with pluripotent mesenchymal differentiation potential. They have been found to have immunosuppressive properties and the ability to modulate angiogenesis and endogenous tissue repair by in vitro and animal studies. Clinical trials have examined the utility of these cells in autoimmune and inflammatory conditions. In particular, in allogeneic hematopoietic stem cell transplant (HSCT), multiple studies have been conducted to explore the use of MSC to treat acute and chronic graft-versus-host disease (GVHD) and for cotransplantation with HSCT to promote HSC engraftment and prevent GVHD. We review here the results of these studies and discuss some challenges of this treatment modality in this disease setting.